Iron storage capacities and associated ferritin gene expression among marine diatoms - Natalie R. Cohen; Elizabeth Mann; Brooke Stemple; Carly M. Moreno; Sara Rauschenberg; Jeremy E. Jacquot; William G. Sunda; Benjamin S. Twining; Adrian Marchetti (Limnology and Oceanography, 2018)
In large regions of the ocean, low iron availability regulates diatom growth and species composition. Diatom species often vary in their physiological response to iron enrichment, with natural and artificial iron additions in iron‐limited regions of the ocean resulting in large blooms of primarily pennate diatoms. The ability of pennate diatoms to proliferate following pulse iron additions has been partly attributed to their ability to acquire and store excess intracellular iron in the iron storage protein ferritin. Recent transcriptome sequencing of diatoms indicate that some centric diatoms also possess ferritin. Using a combination of physiological and molecular techniques, we examined the iron storage capacities and associated ferritin gene expression in phylogenetically diverse centric and pennate diatoms grown under high and low iron concentrations. There were no systematic differences among ferritin‐containing and non‐containing diatom lineages in their ability to store iron in excess of that needed to support maximum growth rates. An exception, however, was the ferritin‐containing pennate diatom Pseudo‐nitzschia granii , native to iron‐limited waters of the Northeast Pacific Ocean. This species exhibited an exceptionally large luxury iron storage capacity and increased ferritin gene expression at high iron concentrations, supporting a role in long‐term iron storage. By contrast, two other diatoms species that exhibited minimal iron storage capacities contained two distinct ferritin genes where one ferritin gene increased in expression under iron limitation while the second showed no variation with cellular iron status. We conclude that ferritin may serve multiple functional roles that are independent of diatom phylogeny.